EFEKTIVITAS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL CABAI MERAH - Erida Nurahmi; T. Mahmud T. Mahmud; Sylvia Rossiana S (Jurnal Floratek, 2011)
The objectives of this experiment were to study effectiveness of organic fertilizer on growth and yield of some varieties of red chili The experiment used a Randomized Complete Block Design with factorial pattern 3 x 3 and 3 replicates. There were 2 factors studied, i.e. organic fertilizer (P1= compost fertilizer, P2= liquid fertilizer, P3= guano fertilizer) and varieties (V1= TM-999, V2= ST-168, V3= local). The result showed that the best fertilizer for red chili growth and yield was guano fertilizer and the best variety was local variety. There was not significant interaction between organic fertilizers and varieties on all growth and yield variables studied.